PANDANGAN ISLAM TENTANG FEMINISME DALAM NOVEL PEREMPUAN BERKALUNG SORBAN - Sari, Diah Oktavia (sarasvati, 2019)
Feminism is movement demands gender between man and woman but islamic religion moreover often considered to be a shackles that muslim girls in even things out of position. In a novel that all the pbs author trying to straighten out to those who believe they are living and misogynist as in treatment a husband with his wife which by the feminist often regarded as shackles and limits for women in particular that muslim girls operate in full freedom in his life as a human.